Hiring costs of skilled workers and the supply of firm-provided training - Marc Blatter; Samuel Mühlemann; Samuel Schenker; Stefan Wolter (Institute for the Study of Labor (IZA), 2012)
This paper analyzes how the costs of hiring skilled workers from the external labor market affect a firm's supply of training. Using administrative survey data with detailed information on hiring and training costs for Swiss firms, we find evidence for substantial and increasing marginal hiring costs. However, firms can invest in internal training of unskilled workers and thereby avoid costs for external hiring. Controlling for a firm's training investment, we find that a one standard deviation increase in average external hiring costs increases the number of internal training positions by 0.7 standard deviations.
urn:nbn:de:101:1-201205026108
Keywords: J23; J24; J32; 330; hiring costs; apprenticeship training; firm-sponsored training; Personalbeschaffung; Grenzkosten; Betriebliches Bildungsmanagement; Schweiz